2017
DOI: 10.1155/2017/6879712
|View full text |Cite
|
Sign up to set email alerts
|

Squalene Extraction by Supercritical Fluids from Traditionally Puffed Amaranthus hypochondriacus Seeds

Abstract: Extraction of squalene, a potent natural antioxidant, from puffed A. hypochondriacus seeds was performed by supercritical fluid extraction (SCFE); besides, to have a blank for comparison, extraction was performed also by Soxhlet method using organic solvents (hexane). Chemical proximal composition and seed morphology were determined in raw, puffed, and SCFE-extracted seeds. Extracts were obtained with a 500 mL capacity commercial supercritical extractor and performed between 10 and 30 MPa at 313, 323, and 333 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…Thus, high‐intensity ultrasound may extensively (break the cell membrane and denature proteins) release the squalene from complex tissue as evidenced by the increased efficiency, compared to the conventional solvent extraction method (Table ) (Halim et al, ). In addition, squalene may undergo weak hydrophobic‐hydrophobic or van der Waals interactions with denatured cellular components (proteins and carbohydrates) generated during the extraction process (Popa et al, ; Rosales‐García et al, ; Spanova and Daum, ). These interactions may be destabilized by ultrasonic cavitation, resulting in increased mobility of squalene to interact with the solvent system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, high‐intensity ultrasound may extensively (break the cell membrane and denature proteins) release the squalene from complex tissue as evidenced by the increased efficiency, compared to the conventional solvent extraction method (Table ) (Halim et al, ). In addition, squalene may undergo weak hydrophobic‐hydrophobic or van der Waals interactions with denatured cellular components (proteins and carbohydrates) generated during the extraction process (Popa et al, ; Rosales‐García et al, ; Spanova and Daum, ). These interactions may be destabilized by ultrasonic cavitation, resulting in increased mobility of squalene to interact with the solvent system.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to its unique functional and structural properties, squalene has numerous applications in nutraceutical, pharmaceutical, cosmetics, and food industries (Bindu et al, ; Spanova and Daum, ). Due to its high commercial demand, the global production of squalene has increased to 2500 ton year −1 in 2013 with a value of 93 million dollars and is expected to rise to 241.9 million dollars by year 2022 (Research, ; Rosales‐García et al, ). Squalene is produced at 1050 ton year −1 from plants (chiefly from olive oil); 1000 ton year −1 is recovered from shark liver (a processing by‐product), and the remainder (450 ton year −1 ) is produced synthetically via genetically modified microorganisms (e.g., Amyris, Inc. (Emeryville, CA, USA) and Biossance (Emeryville)).…”
Section: Introductionmentioning
confidence: 99%
“…This is because of its applications in various industrial products, hence, the need to briefly highlight it. Squalene is a type of unsaponifiable lipid which functions as a biosynthetic precursor, to all steroids (phytosterols and cholesterol) in both plants and animals [6,15]. It is a triterpene (C 30 H 50 ), often found in tissues of plants and animals [15].…”
Section: Introductionmentioning
confidence: 99%
“…Squalene is a type of unsaponifiable lipid which functions as a biosynthetic precursor, to all steroids (phytosterols and cholesterol) in both plants and animals [6,15]. It is a triterpene (C 30 H 50 ), often found in tissues of plants and animals [15]. Many research works have shown the biochemical importance squalene as antioxidant [15][16][17][18], as well as chemopreventive agent [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation